PENGARUH FASILITAS KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS PEMUDA DAN OLAHRAGA PROVINSI SUMATERA SELATAN - Sari, Indah Permata; Mikial, Msy.; Sakarina, Sari (LPPM Universitas Ibnu Sina, 2025)
This study aims to analyze the impact of work facilities, work discipline, and work motivation on employee performance at the Youth and Sports Office of South Sumatra Province. Using a quantitative survey method, the research involved a population of 65 employees from the office. The findings reveal that both work facilities and work discipline have a positive and significant effect on work motivation, which subsequently influences employee performance. Improved work facilities contribute to a more comfortable and productive work environment, while a strong disciplinary framework encourages employees to fulfill their responsibilities more effectively. Interestingly, the study found that work motivation alone does not have a significant impact on employee performance, suggesting that other factors may play a more critical role. This highlights the necessity for government agencies to focus on enhancing physical work conditions and establishing robust disciplinary measures to foster better performance among employees. The results indicate that a well-maintained work environment, combined with strict adherence to discipline, is essential for achieving optimal employee productivity. Therefore, recommendations are made for the Youth and Sports Office to prioritize improvements in facilities and enforce discipline to enhance overall employee performance and organizational effectiveness.